Corporate cultures and global brands - Rothacher, Albrecht (World Scientific Pub., 2004)
This interesting book covers the development of 19 prominent European, American and Asian companies from their humble origins to their current status as global operators. The case studies review the changes of their corporate structures and the successes and failures of their marketing and branding strategies. A wide range of business sectors is covered, including foodstuffs, drinks, retail, apparel, electronics, aviation, cars and entertainment. Of prime importance for corporate survival and growth in all sectors and countries is the crucial shift from owner-founder-run companies to consolida.